Aberrant Blood Vessel Formation Connecting the Glomerular Capillary Tuft and the Interstitium Is a Characteristic Feature of Focal Segmental Glomerulosclerosis-like IgA Nephropathy - Beom Jin Lim; Min Ju Kim; Soon Won Hong; Hyeon Joo Jeong (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background: Segmental glomerulosclerosis without significant mesangial or endocapillary proliferation is rarely seen in IgA nephropathy (IgAN), which simulates idiopathic focal segmental glomerulosclerosis (FSGS). We recently recognized aberrant blood vessels running through the adhesion sites of sclerosed tufts and Bowman's capsule in IgAN cases with mild glomerular histologic change. Methods: To characterize aberrant blood vessels in relation to segmental sclerosis, we retrospectively reviewed the clinical and histologic features of 51 cases of FSGS-like IgAN and compared them with 51 age and gender-matched idiopathic FSGS cases. Results: In FSGS-like IgAN, aberrant blood vessel formation was observed in 15.7% of cases, 1.0% of the total glomeruli, and 7.3% of the segmentally sclerosed glomeruli, significantly more frequently than in the idiopathic FSGS cases (p = .009). Aberrant blood vessels occasionally accompanied mild cellular proliferation surrounding penetrating neovessels. Clinically, all FSGS-like IgAN cases had hematuria; however, nephrotic range proteinuria was significantly less frequent than idiopathic FSGS. Conclusions: Aberrant blood vessels in IgAN are related to glomerular capillary injury and may indicate abnormal repair processes in IgAN.